An experimental study on LPG/H2O2 mixture for combustion - Sharifah Zureehan, Syed Othman (2011)
Liquefied petroleum gas (LPG) has a mark as traditional hydrocarbon structure as conventional fuels. Thus the objective of this research is to study the characteristics of LPG/H202 blends in various compositions in the presence of homogeneous catalyst and controlling the exhaust emission by reducing green house gases. Hydrogen peroxide (11202) is recently reported as fuel combustion enhancer and to be a low-emission highquality fuel blend replacement of hydrogen. Consequently, this research discussed the influence of hydrogen peroxide (11202) combination with LPG in various percentages for combustion. Materials used in this experiment include LPG, hydrogen peroxide (11202) with a concentration of 50% technical grade, homogeneous catalyst and augar.The addition of H202 at various percentages to LPG in LPGIH202 blends will be used for the experiments and measurements can be made to study the characteristics, combustion, and exhaust emissions. A comparative study was carried out to analyze the exhaust emissions from the combustion, the charaterization of fuel blend and the corrosion (copper strip) test according to the ASTM standard. From the experiment, the result shows that 11202 as additive to LPG could contribute to reduction of emissions by decreasing generation of carbon monoxide (CO) in the form of carbon dioxide (CO2)because of excessive oxygen in 11202 Hence, this research contributes to lesser exhaust emissions and hopefully it can be produced and use as alternative fuels for transportation.